Effects of butylphthalide sodium chloride injection combined with edaravone dexborneol on neurological function and serum inflammatory factor levels in sufferers having acute progressive cerebral infarction - Li, Yaqiang; Liu, Jie; Zhu, Yuanyuan; Xue, Min; He, Jiale (Frontiers in Neurology, 2024)
ObjectivesFor investigating an influence on butylphthalide sodium chloride injection combined with edaravone dextromethorphan on neurological function, serum free radical levels, and serum inflammatory factor levels in sufferers having acute progressive cerebral infarction (APCI).MethodsA cohort of 200 patients, afflicted by APCI and admitted to our healthcare institution between December 2018 through July 2023, were incorporated into this longitudinal prospective analysis. Employing a random number table methodology, the patient cohort was bifurcated into a control group (n = 100) and an observation group (n = 100). The control group is treated with butylphthalide sodium chloride injection and the study group is treated with edaravone dexborneol, based on the control group. The posttreatment curative efficacy on the two groups is recorded, and treatment of both the two groups is compared. Before and after neurological function indexes (NIHSS and BI), inflammatory factor indexes (hs-CRP, IL-8, and TNF-a), serum free radical levels (ROS, NO, and SOD), and contrasted between the two groups of treatment effect during therapy.ResultsCompared with the control (65%), the observation group exhibited a significantly higher effective rate of around 89%. In the observation group, the improvement in NIHSS, and Barthel index scores; inflammatory indexes including hs-CRP, IL-8, and TNF-a; and serum free radical levels including ROS, NO, and SOD in peripheral blood was better than the control group, with significant difference (all P<0.05).ConclusionThe clinical efficacy of edaravone dexborneol combined with butylphthalide sodium chloride injection in the treatment of acute progressive cerebral infarction is precise, which can effectively reduce the level of inflammatory factors and serum free radicals in patients, improve the neurological function of patients, and reduce the damage of cerebral cells, and the safety is high.